STRATEGI KIAI DAN SANTRI DALAM MEWUJUDKAN KEMANDIRIAN EKONOMI PONDOK PESANTREN NURUL AMANAH BANGKALAN - Moh Idris; Taufiqur Rahman (PROCEEDING UMSURABAYA, 2022)
The research departs from the importance of identification related to economic independence in Islamic boarding schools, which functions to see the involvement of Kiai and students in realizing the financial autonomy of pesantren phenomenologically because so far pesantren are only seen as Islamic da'wah institutions and educational institutions but pesantren as an institution for community empowerment. In the economic field, there are still many that have not been exposed in detail and in-depth. This study focuses on the goal, knowing the kiai's strategy in realizing the economic independence of the Nurul Amanah Santa Islamic Boarding School and the system of the santri in recognizing the financial autonomy of the pesantren. This method uses a qualitative approach where the data collection technique uses documentation, observation and thorough interviews with the Kiai and several students at the Islamic boarding school. The results of this study conclude 1). The kiai's strategy to realize the economic independence of Islamic boarding schools is to use capacity-building methods, strengthen institutions, transfer knowledge and strengthen networks. 2). The way of the santri in realizing the economic independence of the pesantren as assistant caregivers in learning the financial autonomy of the pesantren.Keywords: Strategy; Kiai; Santri; Economic Independence; Islamic Boarding School